MEKANISME TRANSMISI HARGA INTERNASIONAL DALAM RANGKA PENETAPAN KEBIJAKAN HARGA OLEH PEMERINTAH TERHADAP BEBERAPA KOMODITAS HASIL PERTANIAN TERTENTU - Nuryadin, Didi; Astuti, Rini Dwi; Bhinadi, Ardito (Jurnal Ekonomi & Studi Pembangunan, 2016)
This study aimed to analyze the mechanism of transmission of international prices in the context of preparing the government's policy of controlling prices through the pricing of certain agricultural commodities. This price control in order to ensure stability of prices of agricultural commodities so as to support and ensure the economic stability. The analytical tool used is regression to the data period used was May 2009 to December 2013. The results showed that the increase in retail price increases in producer prices which indicates that the market red peppers, chicken meat and fresh fish are not integrated perfectly. Variation changes in retail prices is a source of variation and the producer price changes have a significant relationship between producer prices at retail prices. Changes in retail prices is not transmitted completely to the producer price which the retail price increases pushed up producer prices.